Transmitting information or engaging in problem exploration? an examination of the effects of educational media designs on students' learning outcomes.[article]. - Gravoso, Rotacio S. .
This study aimed to find out if design of educational media affects learning outcomes. Focusing on ecological problems, two classes studied using media that either transmitted information, or asked students to explore the problems. Another class that did not use any of the two media served as a control group. The variable, learning outcomes, was measured in terms of students' understanding score of ecological problems. A 3 (groups)x2(test) factorial design was use in the analysis. Results showed that the improvement of the exploration group's mean score in the ecological problems studied was consistently higher than the two groups. findings suggest that media's potentials to support quality learning can be harnessed to the fullest extent if these are designed for students to explore problems.